TELA’AH DAN ANALISIS KEBIJAKAN PEMERINTAH TENTANG PENDIDIKAN INKLUSIF - Selamat Maulana; Ahmad Suriansyah; Sulistiyana; Uswatun Nisa (Jurusan Pendidikan Luar Biasa, 2025)
This article examines the Indonesian government's policies on inclusive education, exploring their philosophical, normative-religious, empirical, and juridical foundations. A literature review method is employed to analyze Law No. 20 of 2003 on the National Education System, Law No. 8 of 2016 on Persons with Disabilities, and Ministerial Regulation No. 70 of 2009 on Inclusive Education. The findings reveal that despite the existence of a legal framework, the implementation of inclusive education often faces challenges, such as limited resources, insufficient readiness of educators, and social stigma. This article highlights the importance of shifting societal paradigms toward embracing diversity and strengthening teacher capacity through training. By adopting integrated policies and collaborative approaches, inclusive education can foster a more equitable and diversity-appreciating society. The analysis also underscores the necessity of continuous policy evaluation to ensure the achievement of inclusive education goals in line with social justice principles.